Don't be rejected, how can we help authors, reviewers and editors?: Report of a Symposium for Editors Publishers and Others with an Interest in Scientific Publication, Held in Boston on Wednesday, 11 March 2015, during the Annual Meeting of the International Association for Dental Research. (February 2017) - Eaton, K.A.; Innes, N.; Balaji, S.M.; Pugh, C.; Honkala, E.; Lynch, C.D.
Abstract: This satellite symposium was the fifth in a series for editors, publishers, reviewers and all those with an interest in scientific publishing. It was held on Wednesday, 11 March 2015 at the IADR meeting in Boston, Massachusetts. The symposium attracted more than 210 attendees. The symposium placed an emphasis on strategies to ensure that papers are accepted by peer reviewed journals. The speaker, representing the Journal of Dental Research gave a history of peer review and explained how to access material to advise new authors. The speaker from India outlined the problems that occur when there is no culture for dental research and it is given a low priority in dental education. He outlined remedies. The speaker from SAGE publications described the help that publishers and editors can provide authors. The final speaker suggested that in developing countries it was essential to create alliances with dental researchers in developed countries and that local conferences to which external speakers were invited, stimulated research both in terms of quantity and quality. A wide ranging discussion then took place.